FAKTOR-FAKTOR YANG MEMPENGARUHI KADAR KOLESTEROL PADA PEGAWAI NEGERI SIPIL (PNS) DI PEMDA KABUPATEN GIANYAR PROVINSI BALI - Sukartini Adnyana; Eka Padmiari (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2020)
The purpose of this study was to determine the factors that affect cholesterol levels of civil servants in districts Gianyar Bali Province. This research is an observational study with cross sectional design. The research sample of 68 people consisting of 44 men and 24 women. The results showed that the majority of the sample had a good nutritional status (normal) is 50%, 22.10% fat nutritional status and nutritional status obesity 27.90%. And of samples that have normal cholesterol levels higher at 79.40% compared with the sample hypercholesterolemia 20.60%. Based on the analysis of data obtained using cross table that out of 68 samples, which is the highest percentage of heredity that had hypercholesterolemia on samples that do not have family or relatives that heart disease is equal to 20.6%, Factors affecting cholesterol levels is the activity (work, exercise/sports and recreation irregular) is 11.8%, consuming fat > 25% of the total energy requirement (16.2%).